DEIXIS IN THE SONG LYRICS GOODBYE’S (THE SADDEST WORD) BY CELINE DION - Novita Darni; Purwanto Siwi; Devi Pratiwy (JOURNAL OF LANGUAGE, 2023)
Deixis is used in most conversations or in writing literary works, including song lyrics. The purpose of this research is to reveal the use of deixis in the lyrics of Celine Dion's Goodbye's (The Saddest Word). In this study, the descriptive-qualitative method was used to collect the data. The procedure used to analyze the data starts with collecting data, using deixis, identifying the classification of data usage from person deixis, spatial deixis, and temporal deixis, and making conclusions on the use of deixis data. The theory proposed by Yule was used to analyze and classify the types of deixis. The results showed that the three types of deixis, namely person deixis, spatial deixis, and temporal deixis, are found in the song lyrics, with details of 47 person deixis, 8 spatial deixis, and 8 temporal deixis.